Five views on the church and politics - Black, Amy E. (Grand Rapids, Michigan : Zondervan, 2015)
Few topics can grab headlines and stir passions quite like politics, especially when the church is involved. Considering the attention that many Christian parachurch groups, churches, and individual believers give to politics-and of the varying and sometimes divergent political ideals and aims among them-Five Views on the Church and Politics provides a helpful breakdown of the possible Christian approaches. Readers will find themselves equipped to think more deeply about the relationship between church and state in a way that goes beyond mere policy debates and current campaigns. General Editor Amy Black brings together five top-notch political theologians in the book, each representing one of the five key political traditions within Christianity: Anabaptist (Separationist)-Thomas Heilke Lutheran (Two Kingdom)-Robert Benne Catholic (In Tension)-J. Brian Benestad Reformed (Integrationist)-James K. A. Smith Black Church (Prophetic)-Bruce Fields Each author addresses his tradition's theological distinctives, the role of government, the place of individual Christian participation in government and politics, and how churches should (or should not) address political questions. Responses by each contributor to opposing views will highlight key areas of difference and disagreement. Thorough and even-handed, Five Views on the Church and Politics will enable readers to consider the strengths and weaknesses of the most significant Christian views on political engagement and to draw their own, informed conclusions. -- Provided by publisher.
Introduction: Christian traditions and political engagement / Amy E. Black -- The Anabaptist (separationist) view / Thomas W. Heilke -- Responses: A Lutheran response / Robert Benne ; A Black church response / Bruce L. Fields ; A Reformed response / James K.A. Smith ; A Catholic response / J. Brian Benestad -- The Lutheran (paradoxical) view / Robert Benne -- Responses: An Anabaptist response / Thomas W. Heilke ; A Black church response / Bruce L. Fields ; A Reformed response / James K.A. Smith ; A Catholic response / J. Brian Benestad -- The Black church (prophetic) view / Bruce L. Fields -- Responses: An Anabaptist response / Thomas W. Heilke ; A Lutheran response / Robert Benne ; A Reformed response / James K.A. Smith ; A Catholic response / J. Brian Benestad -- The Reformed (transformationist) view / James K.A. Smith -- Responses: An Anabaptist response / Thomas W. Heilke ; A Lutheran response / Robert Benne ; A Black church response / Bruce l. Fields ; A Catholic response / J. Brian Benestad -- The Catholic (synthetic) view / J. Brian Benestad -- Responses: An Anabaptist response / Thomas W. Heilke ; A Lutheran response / Robert Benne ; A Black church response / Bruce L. Fields ; A Reformed response / James K.A. Smith -- Conclusion: Christian witness in the public square / Amy E. Black.
Includes bibliographical references and indexes.
Keywords: Christianity and politics; Theology, Doctrinal